The BP Gulf of Mexico oil spill. Part 1 - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
On April 20, 2010, BP's offshore drilling rig, the Deepwater Horizon, exploded in the Gulf of Mexico and caused the largest accidental marine oil spill in history. This case examines the tragic effects of the accident and sheds light on the reasons that caused it.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The BP Gulf of Mexico Oil Spill: Part 1. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 137-141). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; BP Deepwater Horizon Explosion and Oil Spill, 2010.; Drilling platforms -- Accidents -- Mexico, Gulf of; Oil pollution of the sea -- Mexico, Gulf of; Industrial safety -- Management -- Case studies